For Fifth Consecutive Year India Drove Private Activity in Infrastructure in South Asia to a New Peak in 2010 - World Bank (Washington, DC, 2012)
In 2010, 102 infrastructure projects with private participation reached financial or contractual closing in 4 low- and middle-income countries in South Asia, involving investment commitments of US$47 billion. Infrastructure projects implemented in the 1990-2009 period attracted new investment of US$26.5 billion, bringing total investment commitments (hereafter, investment) to infrastructure sectors to US$73.5 billion in 2010. The activity in 2010 represents an increase of 72 percent by investment and 70 percent by number of projects compared with 2009. The growth rate of investment is particularly significant given that investment in the region had been growing since 2006 but at a lower rate. Investment in new projects grew by 54 percent from 2009, and additional investment in projects implemented in 1990-2009 rose by almost 120 percent.